The Use of Google Classroom in Learning Writing Descriptive Text: Students’ Perceptions - Kartika Febiyanti; Mansyur Srisudarso; Praditya Putri Utami (Journal of Languages and Language Teaching, 2021)
Writing is one of the four essential language skills for language learning. Writing is considered important because it's one of the communication medium and it makes student critical. However, writing is a significant difficulty for both native and non-native learners. Due to advancements in technology, LMS enables educators and students to communicate and engage in new ways. Google Classroom, being one of the most widely used LMS platforms, may assist students in developing their ability to write a descriptive text. This research aimed to investigate students’ perception of using Google Classroom in learning writing descriptive text. The subject examined students in the tenth grade at a Senior High School in Indonesia. This research used a qualitative approach with a narrative inquiry. The researcher utilized semi-structured interviews to gather the data and analyzed them using the thematic analysis of Braun & Clarke. The indicator of the research question is based on UTAUT (Unified Theory of Acceptance of Technology) by Vankavesh (2003). The study discovered that students preferred using Google Classroom to learn descriptive text. Google Classroom helps them to know and understand descriptive writing materials easily. However, Effort Expectancy may be altered with sufficient internet use and Google Classroom upgrades.